Toleransi terhadap gratifikasi sebagai prediktor korupsi: Studi komparasi Indonesia dan Hong Kong (Komisi Pemberantasan Korupsi, 2023)
Corruption is a global problem faced by every country and culture around the world. Since overt corrupt behaviour does not develop in a person overnight, it is therefore important to identify the more proximal and benign forms of corruption. In this research, taking advantage of the cultural and corruption perception index differences between Indonesia and Hong Kong, we conducted a qualitative study on the phenomenon of gratification, the act of giving a public officer monetary or physical rewards for a service they provide, even though the service is within their job description. The research subjects were drawn from Hong Kong and Indonesian college students or fresh graduates. During the interview, we found striking differences between Hong Kong and Indonesian respondents in terms of the experience of being asked for a reward, the perception and urge to give a reward, and the tendency to accept a reward during a public service transaction. Indonesian respondents are generally more exposed, familiar, and permissive to gratification than their Hong Kong counterparts. The reasons for this phenomenon were then investigated and a possible correlation of this permissiveness with the country’s corruption perception index was then discussed. It is suggested that corruption eradication must be accompanied by sociocultural and educational intervention toward naïve subjects, thus preventing them from being permissive to gratification, which can act as the proxy for active corruption in the future.